ISLAMIC ORIGINALITY (FITRAH) AND ITS REALIZATION IN ISLAMIC EDUCATION: A TRANSDISCIPLINARY SCIENTIFIC - Napitupulu, Dedi Sahputra (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This research aims to investigate the notion of Islamic originality (fitrah) and its realization in Islamic education from a transdisciplinary scientific standpoint. Fitrah is a potential or tendency carried by humans from birth and largely determines the future success of humans themselves. Because these tendencies vary, analyzing the fitrah of different disciplines is also very important. This research employs a qualitative literature analysis approach by tracking numerous authoritative publications. The findings of this study reveal that nature is an inherent human capability that already exists in every individual. As the theological foundation, the Qur'an and Hadith have offered a wealth of material on the significance of potential human growth. History has also revealed that the advancement of Islam in the past was attributable to the rulers' assistance in cultivating the talents and abilities of Muslim scholars, who went on to create several magnificent accomplishments. Ultimately, education is the only means of maximizing human potential.